An Exploratory Study of the Quality of English Teacher Education Programs at Malaysian Tertiary Institutions: How is Quality Achieved - Issa, Jinan Hatem; Jamil, Hazri (International Journal of Asian Social Science, 2014)
In response to the growing competition among Malaysian tertiary institutions to enrol students, education quality has become a key concern. The quality of English teacher education is critical and is a focus of the English Language Teaching profession. The current study was undertaken to explore the quality of English teacher education by measuring the indicators of four forms of capital (intellectual, financial, spiritual, and social) as determinants of quality. Sixty-nine heads and lecturers of English teacher education programs at five Malaysian major public tertiary institutions participated in the study; they completed questionnaires containing forty indicators of ‘self-assessment’. The findings indicated the highest and lowest indicators of each of the four forms of capital. Additionally, some significant positive correlations were reported among the four forms of capital. These results demonstrated that academic staff should continuously change, adapt, and learn to not get left behind. Most importantly, executives in English teacher education programs at Malaysian public tertiary institutions should lead, rather than follow, in the development of quality programs.